2015
DOI: 10.4238/2015.december.21.13
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of single nucleotide polymorphisms in patients with atrophic age-related macular degeneration in oldest old Han Chinese

Abstract: ABSTRACT. The aim of this study was to identify disease-associated loci in oldest old Han Chinese with atrophic age-related macular degeneration (AMD). This genome-wide association study (GWAS) only included oldest old (≥95 years old) subjects in Rugao County, China. Thirty atrophic AMD patients and 47 age-matched non-AMD controls were enrolled. The study subjects underwent a complete ophthalmic examination. Genomic DNA was extracted from peripheral blood samples. Single nucleotide polymorphisms (SNPs) were sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In present study, we compared the frequencies of 39 SNPs of 16 genes between 193 AMD patients and 404 controls from Chinese Tujia ethnic minority group. It had reported that ARMS2 and CFH variants were associated with neovascular AMD in the Thai, Korean and Chinese Han population [2830] and no previous studies focused on the associations between SNPs and AMD in Tujia ethnic minority group. Therefore, we designed this research to identify the potential associations.…”
Section: Discussionmentioning
confidence: 99%
“…In present study, we compared the frequencies of 39 SNPs of 16 genes between 193 AMD patients and 404 controls from Chinese Tujia ethnic minority group. It had reported that ARMS2 and CFH variants were associated with neovascular AMD in the Thai, Korean and Chinese Han population [2830] and no previous studies focused on the associations between SNPs and AMD in Tujia ethnic minority group. Therefore, we designed this research to identify the potential associations.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of history, millions of mutations in the human genome have accumulated, resulting in genetic variations such as single nucleotide polymorphisms (SNPs). These single base changes in the DNA sequence occur relatively frequently (>1 percent) and have been the subject of much study [ 34 , 35 , 36 , 37 , 38 , 39 , 40 ], especially prior to the wide availability of whole genome sequencing. In AMD, familial-based linkage [ 41 , 42 , 43 , 44 , 45 ] and genome-wide association studies (GWAS) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 ] have rapidly uncovered a large number of common and rare disease-associated gene variants [ 53 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the course of history, millions of mutations in the human genome have accumulated, resulting in genetic variations such as single nucleotide polymorphisms (SNPs). These single base changes in the DNA sequence occur relatively frequently (>1 percent) and have been the subject of much study [34][35][36][37][38][39][40], especially prior to the wide availability of whole genome sequencing. In Age is the strongest demographic risk factor for the development of AMD [13,14,20].…”
Section: Introductionmentioning
confidence: 99%
“…To identify genetic variants associated with GA in a Han Chinese population, a small GWAS analysis was performed in GA patients older than age 90 compared to matched controls (Zhou et al., 2015). While statistically significant loci were not detected due to the small sample size, suggestive hits included a locus on chromosome 4 near the VEGF‐C gene.…”
Section: Genetic Biomarkers Associated With Gamentioning
confidence: 99%